A model for the role of emotional intelligence in patient safety - Estelle Codier; David Codier (Elsevier, 2015)
Medical errors are the third leading cause of death in the USA, resulting in over 440,000 deaths/year. Although over a decade has passed since the first Institute of Medicine study that documented such horrific statistics and despite significant safety improvement efforts, serious progress has yet to be achieved. It is estimated that 80% of medical errors result from miscommunication among health care providers and between providers and patients. There is preliminary research evidence that communication skills programs can improve safety outcomes, but a systematic theoretical framework for such programs has not been identified. Because of the connection between emotional intelligence (EI) ability and communication effectiveness, EI has been called by some "one of the largest drivers of patient safety." Little literature has explored this relationship. The purpose of this article was to present a theoretical model for the relationship between EI, communication and patient safety, with conceptual and clinical illustrations used to describe such a relationship.